2004
DOI: 10.1007/978-3-540-24688-6_89
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Coupled Physical and Biogeochemical Ocean Predictions: A Conceptual Basis

Abstract: Abstract. Physical and biogeochemical ocean dynamics can be intermittent and highly variable, and involve interactions on multiple scales. In general, the oceanic fields, processes and interactions that matter thus vary in time and space. For efficient forecasting, the structures and parameters of models must evolve and respond dynamically to new data injected into the executing prediction system. The conceptual basis of this adaptive modeling and corresponding computational scheme is the subject of this prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 7 publications
(10 reference statements)
0
15
0
Order By: Relevance
“…It can be observed that the trajectory of the center of the formation is smoother than the actual level curve with spatial noise. In order to test our current algorithms on realistic ocean fields, we use a snapshot of the temperature field near Monterey Bay produced by the Harvard Ocean Prediction System (HOPS) [57]. This field reflects the temperature at 20 meters below sea surface on 00:00 GMT August 13th, 2003.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…It can be observed that the trajectory of the center of the formation is smoother than the actual level curve with spatial noise. In order to test our current algorithms on realistic ocean fields, we use a snapshot of the temperature field near Monterey Bay produced by the Harvard Ocean Prediction System (HOPS) [57]. This field reflects the temperature at 20 meters below sea surface on 00:00 GMT August 13th, 2003.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…For example, upwelling events in the ocean bring nutrient-rich, cold water from the sea bottom to the surface where phytoplankton, which need to consume iron but also need the sun for photosynthesis, can gather and grow. Accordingly, understanding the physical oceanography and how it couples with the biological dynamics is necessary for tackling a number of important open problems [1], [2].…”
Section: Central Objectivementioning
confidence: 99%
“…Since reduced uncertainty implies better measurement coverage, we also refer to this as a coverage metric. In ongoing work [2], [35], [36], [37], information that can be inferred from a dynamical model is included into the metric used to control vehicles.…”
Section: B Problem Definitionmentioning
confidence: 99%
See 2 more Smart Citations